The state of Pauline studies: a survey of recent research - Gupta, Nijay K.; Heim, Erin M.; McKnight, Scot (Baker Academic, a division of Baker Publishing Group, 2024)
"A diverse team of leading scholars survey the current landscape of Pauline studies, offering readers a concise guide to contemporary discussions"--